Evaluation of options for harvest of a recombinant E. Coli fermentation producing a domain antibody using ultra scale‐down techniques and pilot‐scale verification. (12th January 2016) - Voulgaris, Ioannis; Chatel, Alex; Hoare, Mike; Finka, Gary; Uden, Mark
Abstract : Ultra scale‐down (USD) methods operating at the millilitre scale were used to characterise full‐scale processing of E. coli fermentation broths autolysed to different extents for release of a domain antibody. The focus was on the primary clarification stages involving continuous centrifugation followed by depth filtration. The performance of this sequence was predicted by USD studies to decrease significantly with increased extents of cell lysis. The use of polyethyleneimine reagent was studied to treat the lysed cell broth by precipitation of soluble contaminants such as DNA and flocculation of cell debris material. The USD studies were used to predict the impact of this treatment on the performance and here it was found that the fermentation could be run to maximum productivity using an acceptable clarification process (e.g., a centrifugation stage operating at 0.11 L/m 2 equivalent gravity settling area per hour followed by a resultant required depth filter area of 0.07 m 2 /L supernatant). A range of USD predictions was verified at the pilot scale for centrifugation followed by depth filtration. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 32:382–392, 2016